2022
DOI: 10.3390/systems10060263
|View full text |Cite
|
Sign up to set email alerts
|

Haze Risk Assessment Based on Improved PCA-MEE and ISPO-LightGBM Model

Abstract: With the economic development in China, haze risks are frequent. It is important to study the urban haze risk assessment to manage the haze disaster. The haze risk assessment indexes of 11 cities in Fenwei Plain were selected from three aspects: the sensitivity of disaster-inducing environments, haze component hazards and the vulnerability of disaster-bearing bodies, combined with regional disaster system theory. The haze hazard risk levels of 11 cities in Fenwei Plain were evaluated using the matter-element e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The study highlighted ozone’s strong correlation with PM 2.5 and weak correlation with SO 2 , using China as a case study. Besides, other studies found that the meta-algorithms significantly improved the performance of the forecasting models hence obtaining higher forecasting results 28 . Furthermore, an innovative model combining Wavelet Transform (WT), Stacked Autoencoder (SAE), and Long Short-Term Memory (LSTM) has been introduced by some researchers for precise PM 2.5 prediction 29 .…”
Section: Introductionmentioning
confidence: 98%
“…The study highlighted ozone’s strong correlation with PM 2.5 and weak correlation with SO 2 , using China as a case study. Besides, other studies found that the meta-algorithms significantly improved the performance of the forecasting models hence obtaining higher forecasting results 28 . Furthermore, an innovative model combining Wavelet Transform (WT), Stacked Autoencoder (SAE), and Long Short-Term Memory (LSTM) has been introduced by some researchers for precise PM 2.5 prediction 29 .…”
Section: Introductionmentioning
confidence: 98%
“…Wang et al 25 added an attention mechanism to the model to improve the prediction accuracy of the LSTM model. Dai et al 26 established five haze hazard risk assessment models by improving theparticle swarm optimization (IPSO) light gradient boosting machine (LightGBM) algorithm and a hybrid model combining XGBoost, four GARCH models and MLP model (XGBoost-GARCH-MLP) is proposed to predict PM2.5 concentration values and volatility 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The proposed model has good performance in the long-term forecasting process. Dai Hongbin et al 18 used the matter-element extension (MEE) model to evaluate the haze hazard risk levels in different cities, and the indicator weights were determined by improving the principal component analysis (PCA) method using the entropy weight method. Finally, several risk assessment models were established by improving the particle swarm optimization (IPSO) light gradient boosting machine (LightGBM) algorithm.…”
Section: Introductionmentioning
confidence: 99%